Peran Pemerintah dalam Pemberian Program MBG (Program Makanan Bergizi Gratis) - Tamaulina Br. Sembiring; Annisa Nabila Sitepu; Ago Rivaldo Toraja Sitepu; M Alief Rizky; Alvin Jonathan Siagian; M Haekal Fajri (Journal of Innovative and Creativity, 2025)
Child hunger and malnutrition remain significant public health issues in Indonesia. The government has implemented targeted interventions such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), and the school free lunch initiative. The free lunch program aims to improve children's daily nutritional intake and reduce stunting prevalence. While promising, the program's effectiveness is hindered by logistical constraints, fiscal limitations, and uneven implementation across regions.